Infrastructure Gaps in Rapidly Expanding Urban Areas: A Case Study of Taluka Khairpur - Mairaj Ali; Nijah Akram; Rimsha Imran (Dialogue Social Science Review (DSSR), 2025)
This study examines the migration patterns and their impact on urban planning in Taluka Khairpur, a rapidly urbanizing region in Sindh, Pakistan. The research aims to understand the primary factors driving migration to urban areas and the associated challenges urban planners face in managing population growth. A survey-based methodology was used to gather data from migrants in Taluka Khairpur, focusing on the reasons for migration, housing conditions, infrastructure availability, and perceptions of urban planning. The results reveal that economic opportunities (45%) are the primary motivator for migration, followed by access to healthcare and education (30%). However, migrants face significant challenges, including difficulties finding affordable housing (70%) and inadequate urban infrastructure (60%). Overcrowding and dissatisfaction with current urban planning efforts were also prevalent, with 65% of respondents expressing concerns about the city's ability to manage rapid urbanization. The study highlights the need for comprehensive urban planning strategies that prioritize affordable housing, infrastructure expansion, and the integration of migrant needs into the planning process. The findings suggest that Taluka Khairpur's urban planning must adapt to the demands of its growing population to ensure sustainable development and improve the quality of life for all residents.